Perancangan Sistem Informasi Pencatatan Bantuan Dinas Gubernur Sumatra Utara Berbasis Website - Yuliana, Ananda; Yahfizham (Jurnal Sistem Informasi Galuh, 2024)
The social assistance data collection process at the People's Welfare Bureau of the Regional Secretariat of North Sumatra Province experiences several problems such as low efficiency and limited data accessibility. This research aims to design and implement an interactive and responsive web-based information system to record official assistance. This solution is expected to improve data processing efficiency and information accessibility for interested parties and the general public. The methodology used in designing this system is the Unified Modelling Language (UML) approach, which includes various types of diagrams such as use case, sequence, activity, and class diagrams. The implementation of this system includes user training, regular maintenance, and information transparency policies. The results of this study show that the designed system can optimise the online data collection process, increase transparency, and facilitate active community participation. In addition, collaboration between departments can also be improved through easy information sharing features. Thus, the new information system has a positive impact in improving the quality of services to people with social welfare problems (PMKS) and recipients of social assistance within the Regional Secretariat of North Sumatra Province.